Exploring the Strategies Employed by Kindergarten Teachers in China to Foster Self-regulation Skills among Young Children - Guo, Yefan (Transactions on Social Science, Education and Humanities Research, 2024)
The self-regulation support strategies employed by Chinese kindergarten teachers and the challenges they face when implementing these strategies are investigated. Self-regulation is considered a crucial aspect of school readiness, and this study focuses on children aged 3-6 years. Through a qualitative approach that involves interviews with six kindergarten teachers, this study explores the different strategies used by teachers to promote self-regulation among young children. The findings show that Chinese kindergarten teachers use various techniques, including games, pretend play, music and songs and picture books, to help children develop their self-regulation skills. However, teachers may encounter challenges such as children not engaging in the activities and a lack of experience among the teachers themselves. In this study, the importance of effective self-regulation support strategies in early childhood education is highlighted, and insights are also provided into the specific approaches used by Chinese kindergarten teachers.